Reduced Apolipoprotein M and Adverse Outcomes Across the Spectrum of Human Heart Failure. Issue 18 (5th May 2020) - Chirinos, Julio A.; Zhao, Lei; Jia, Yi; Frej, Cecilia; Adamo, Luigi; Mann, Douglas; Shewale, Swapnil V.; Millar, John S.; Rader, Daniel J.; French, Benjamin; Brandimarto, Jeff; Margulies, Kenneth B.; et al.
Abstract : Background: Apo (apolipoprotein) M mediates the physical interaction between high-density lipoprotein (HDL) particles and sphingosine-1-phosphate (S1P). Apo M exerts anti-inflammatory and cardioprotective effects in animal models. Methods: In a subset of PHFS (Penn Heart Failure Study) participants (n=297), we measured apo M by Enzyme-Linked ImmunoSorbent Assay (ELISA). We also measured total S1P by liquid chromatography–mass spectrometry and isolated HDL particles to test the association between apo M and HDL-associated S1P. We confirmed the relationship between apo M and outcomes using modified aptamer-based apo M measurements among 2170 adults in the PHFS and 2 independent cohorts: the Washington University Heart Failure Registry (n=173) and a subset of TOPCAT (Treatment of Preserved Cardiac Function Heart Failure With an Aldosterone Antagonist Trial; n=218). Last, we examined the relationship between apo M and ≈5000 other proteins (SomaScan assay) to identify biological pathways associated with apo M in heart failure. Results: In the PHFS, apo M was inversely associated with the risk of death (standardized hazard ratio, 0.56 [95% CI, 0.51–0.61]; P <0.0001) and the composite of death/ventricular assist device implantation/heart transplantation (standardized hazard ratio, 0.62 [95% CI, 0.58–0.67]; P <0.0001). This relationship was independent of HDL cholesterol or apo AI levels. Apo M remained associated with death (hazard ratio, 0.78 [95% CI, 0.69–0.88]; P <0.0001) and the composite of death/ventricular assist device/heart transplantation (hazard ratio, 0.85 [95% CI, 0.76–0.94]; P =0.001) in models that adjusted for multiple confounders. This association was present in both heart failure with reduced and preserved ejection fraction and was replicated in the Washington University cohort and a cohort with heart failure with preserved ejection fraction only (TOPCAT). The S1P and apo M content of isolated HDL particles strongly correlated ( R =0.81, P <0.0001). The top canonical pathways associated with apo M were inflammation (negative association), the coagulation system (negative association), and liver X receptor/retinoid X receptor activation (positive association). The relationship with inflammation was validated with multiple inflammatory markers measured with independent assays. Conclusions: Reduced circulating apo M is independently associated with adverse outcomes across the spectrum of human heart failure. Further research is needed to assess whether the apo M/S1P axis is a suitable therapeutic target in heart failure. Abstract : Supplemental Digital Content is available in the text.